Coexistência de resistência à insulina e elevada tolerância à glicose em ratas prenhes : um mecanismo fisiológico para manutenção da glicemia - Carrara, Márcia aparecida (2013)
During the pregnancy there is an increased risk of hyperglycemia (gestational diabetes) and hipoglycemia. For this reason, it was investigated the insulin resistance (IR) and glucose tolerance (GT) in pregnant rats (PR) and no pregnant rats (NPR). Female Wistar rats with 0 (NPR), 7 (PR day 7), 14 (PR day 14) and 20 (PR day 20) days of pregnancy were used. For conventional insulin tolerance test (ITT) or glucose tolerance test (GTT) female rats were fasted (12h) and received intraperitoneal regular insulin (1 U / kg) or oral glucose (1 g/kg) by gavage. To evaluate glycemia, the blood was collected 0, 10, and 60 min after of insulin (ITT) or glucose (GTT) administration. The conventional ITT and GTT were repeated using the RT-CGMS (Real-time Continuous Glucose Monitoring System) technique. Moreover, It was used the liver perfusion technique to evaluate gluconeogenesis, inferred by the hepatic glucose production (HGP) from alanine (5mM), glutamine (5mM) and glycerol (2mM) in the fasted state (12 h) and the glycogen catabolism (glycogenolysis) induced by adrenaline in the fed state. After insulin administration (conventional ITT), the blood glucose reduction between 0 and 60 min was 70%, 72%, 68% and 55% for NPR group (day 0), PR (day 7), PR (day 14), and PR (day 20), respectively. Moreover, after oral administration of glucose (conventional GTT) the increase of glycemia between 0 to 10 min was 87%, 87%, 60% and 60% for the NPR group (day 0), PR (day 7), PR (day 14), and PR (day 20), respectively. Since, the conventional ITT and GTT demonstrated the coexistence of IR and increased GT in PR group (day 20), this group was used in the subsequent experiments. The kinetic of glucose concentration according to the RT-CGMS showed lower glucose concentration in the fasted and fed state to the PR group (day 20) in comparison with NPR group (day 0). Moreover, the ITT and GTT evaluated by RT-CGMS showed higher IR and GT, respectively (PR group - day 20 vs. NPR group - day 0). On the other hand, the PR (day 20) group showed lower (p <0.05) HGP from alanine and glutamine and higher HGP (p<0.05) from glycerol in comparison with NPR group (0 day). However, the basal rates of glycogenolysis and its activation induced by adrenaline were similar (PR - day 20 vs. NPR -day 0). The HGP from gluconeogenesis and glycogenolysis did not contribute to the glycemic changes of the pregnant rats. However, the coexistence of IR and increased GT during the late pregnancy may represent an important physiological mechanism to permit glucose availability to sustain the rapid fetal growth during late pregnancy and prevent hypoglycemia during fasting.